2016
DOI: 10.1021/acs.jpca.6b09318
|View full text |Cite
|
Sign up to set email alerts
|

Threshold Collision-Induced Dissociation of Proton-Bound Hydrazine and Dimethylhydrazine Clusters

Abstract: Threshold collision-induced dissociation (TCID) using a guided ion beam tandem mass spectrometer is performed on (NH)H where n = 2-4 and on the proton-bound unsymmetrical 1,1-dimethylhydrazine (UDMH) dimer complex. The primary dissociation pathway for all reactants consists of loss of a single hydrazine (or UDMH) molecule followed by the sequential loss of additional hydrazine molecules at higher collision energies for n = 3 and 4. The data were analyzed using a statistical model after accounting for internal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 78 publications
0
10
0
Order By: Relevance
“…As a source of HONO, the reactions of HD/MMH+N 2 O 4 are extensively investigated in experiment and theory [24] . HD, as a high moisture absorbent, is usually present in the form of N 2 H 4 ⋅H 2 O, [29] and its hydrates and protonated‐hydrates are widely studied in compound organic chemistry [30–31] . Turpin et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a source of HONO, the reactions of HD/MMH+N 2 O 4 are extensively investigated in experiment and theory [24] . HD, as a high moisture absorbent, is usually present in the form of N 2 H 4 ⋅H 2 O, [29] and its hydrates and protonated‐hydrates are widely studied in compound organic chemistry [30–31] . Turpin et al.…”
Section: Introductionmentioning
confidence: 99%
“…[24] HD, as a high moisture absorbent, is usually present in the form of N 2 H 4 •H 2 O, [29] and its hydrates and protonated-hydrates are widely studied in compound organic chemistry. [30][31] Turpin et al have noted that organic nitrates can be formed in the wet aerosols with the presence of NO x . [32] Hence the effect of H 2 O on the atmospheric reactions in the presence of HD and MMH should be further taken into consideration.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, we have used guided ion beam tandem mass spectrometry and quantum chemistry to explore the thermochemistry of protonated hydrazine and UDMH and their clusters. [14][15][16] Protonated hydrazine, N 2 H 5 + , was observed to dissociate by homolytic and heterolytic N-N bond cleavages. 16 The thresholds for these processes showed that these dissociations occur along non-adiabatic pathways forming the excited NH 3 + ( 2 A 2 00 ) + NH 2 ( 2 A 1 ) and NH 2 + ( 1 A 1 ) + NH 3 ( 1 A 1 ) product asymptotes, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…16 For the (N 2 H 4 ) n H + clusters where n = 2-4, the primary dissociation pathway for all reactants consists of loss of a single hydrazine molecule followed by the sequential loss of additional hydrazine molecules at higher collision energies for n = 3 and 4, such that sequential binding energies could be ascertained. 15 In that study, a theoretical potential energy surface (PES) that links four low-energy conformers of the (N 2 H 4 ) 2 H + dimer was characterized. The protonbound dimer of UDMH dissociates by loss of neutral UDMH, such that the dimer bond dissociation energy (BDE) could be measured.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation